Wrought Aluminium Alloy Corrosion Propensity in Domestic Food Cooking Environment. (17th October 2012) - Adeosun, S. O.; Akpan, E. I.; Balogun, S. A.
Abstract : The study on corrosion behaviour of wrought aluminium alloy in domestic food cooking conditions has been examined using the gravimetric approach. Flat cold rolled and annealed sheets were subjected to solutions of Capsicum annuum, L. esculentum, Allium cepa, and their blend under three conditions, namely, heating and cooling in still air, heating and cooling in refrigerator, and leaving some in open still atmosphere. Results show that corrosion occurred within the test period (288 hours) in the test environments. There was severe degradation within the first 70 hours of test when coupons were heated and cooled while unheated coupon showed low corrosion propensity. Microstructural analysis show the presence of corrosion pits on coupon surface with second phase particles sandwiched in α -aluminium matrix. Immersed coupon in the blend media show higher number of pits on the surface. Rapid corrosion of wrought aluminium alloy in Capsicum annuum, L. esculentum and Allium cepa media is attributed to the presence of corrosion aggressive elements such as allicin, diallyl-disulphide, and allyl-propyl disulphide present in the corrosion media.